Track-Bridge Interaction Effects in Heavy Haul Railway Viaducts - Ngwenya, Mixo (Department of Civil Engineering, 2023)
When continuously welded rails are placed over a bridge, the track and the bridge interact via the ballast in the case of ballasted track or track slab in the case of non-ballasted track. This interaction, commonly referred to as track-bridge interaction results in force transfer between the track and the bridge. With the demand to increase freight haulage on heavy haul railway lines intensifying to meet mineral export demands, there is a need to understand the manifestation of rail bridge interactions in heavy haul railway bridges. Understanding the manifestation of these forces is critical for the management of the infrastructure during operation. Whilst track-bridge interactions effects design limits in high-speed rail have been documented, to the author's knowledge there has been no documented report that addresses track bridge interactions in the design of new heavy haul railway bridges and the management old heavy haul railway bridges. Resultantly, this study explored the observed patterns of rail forces, longitudinal deck displacements, ambient temperature, concrete temperature and rail temperature on the Olifants River Railway Bridge. Thereafter, the observed patterns were used investigate the effect of rail temperature variation on rail forces and the longitudinal displacement of the deck. Examine the effect of variation in concrete temperature on the longitudinal deck displacement, rail forces and variation in rail temperature as well as the effect of longitudinal deck displacement on rail forces. The effects of the presence of a train on the longitudinal displacement of the deck, rail forces and concrete temperature will also be investigated. Finally, this study developed a predictive multiple linear regression model that will assist in the management and maintenance heavy haul railway bridges. This study demonstrated that rail temperature variation is inversely proportion to the rail forces in the rail, longitudinal deck displacement is directly proportional to concrete temperature variation and that longitudinal deck displacement of the bridge deck and rail forces in the rail are inversely proportional. However, the correlation between the longitudinal deck displacement and the rail temperature, rail temperature in the track and concrete temperature in the deck, concrete temperature in the deck and the rail forces in the track could not be established conclusively. The effect of the presence of the train on the longitudinal displacement of the deck, rail forces and concrete temperature could also not be established conclusively